A multi-element coated modified single crystal nickel cobalt manganese oxide positive electrode material and preparation method thereof and lithium ion battery
Through the multi-coated modification technology, Al compound, W compound and a small amount of lithium source are used to coat single-crystal nickel-cobalt lithium manganate positive electrode material at high temperature, which solves the problem of its high-temperature cycle capacity retention rate under high charging cutoff voltage. Excellent and high-temperature storage internal resistance growth and gas production problems, achieving a more stable surface structure and excellent electrochemical performance.
Patent Information
- Application Number
- CN202211708439.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-29
AI Technical Summary
Single-crystal nickel-cobalt lithium manganate positive electrode material exhibits poor high-temperature circulation capacity retention rate, high-temperature storage internal resistance growth and gas production problems under high charging cutoff voltage, and its surface structure is insufficient.
By using a multivariate coating modification method, the single-crystal nickel cobalt lithium manganate positive electrode material is combined with Al compound, W compound and an additional small amount of lithium source at high temperature to form stable Al2(WO4)3 and lithium tungstate The compound coats the layer to inhibit the diffusion of Al elements and improve the stability of the surface structure of the material.
Significantly improves the capacity, magnification and circulation performance of single-crystal nickel-cobalt-manganese oxide positive electrode material, reduces the poor retention rate of high-temperature circulation capacity, the growth of high-temperature storage internal resistance and gas production problems, and improves the surface structure stability of the material .
Smart Images

Figure CN115863602B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a single crystal nickel-cobalt-manganese positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As new energy vehicles develop, people's requirements for driving range are constantly increasing. Therefore, it is crucial to develop high-energy, high-power density and lower-cost lithium-ion batteries for lithium battery cathode materials. Ternary nickel-cobalt-manganese oxide cathode materials have obvious advantages in capacity and cost compared to lithium cobalt oxide due to their low Co content and high capacity characteristics.
[0003] There are currently two development directions for nickel-cobalt-manganese-oxide lithium cathode materials, which are mainly distinguished from morphology and are divided into secondary spherical morphology particles and single crystal morphology particles. At present, there are relatively mature preparation methods for these two types of materials. The Chinese patent document with application number 201811382498.7 introduces a method for preparing secondary spherical morphology materials, and prepares secondary spherical morphology cathode materials; secondary spheres have a higher energy density due to their smaller primary particles, but are more used in the field of energy storage due to the constraints of factors such as poor high-temperature cycle, fast high-temperature DCR growth, and gas production, and are less used in the power field. The Chinese patent document with application number 201710883429.3 introduces a method for preparing single crystal materials, and prepares single crystal morphology cathode materials. Single crystal ternary cathode materials, due to their larger primary particles and complete structure, have weak anisotropy of lattice expansion and contraction between grains during the cycle, ensuring that they maintain structural integrity during repeated cycles, thereby improving cycle stability. In addition, the low specific surface area and excellent structural stability of single crystal materials work together to improve the cycle stability, and the original morphology of the particles can still be maintained after long cycles. It is currently widely used in the new energy industry.
[0004] Generally speaking, the primary particle design of single crystal ternary cathode materials is large, which leads to low energy density and poor power performance. The main method for improving the energy density of single crystal materials is to increase the cut-off voltage. However, as the cut-off voltage continues to increase ≥4.35V, the surface of the material will undergo a structural transformation from a layered structure to a spinel and then to a NiO rock salt phase. When lithium ions are repeatedly intercalated and deintercalated, due to the anisotropy of the crystal, intracrystalline cracks will occur inside the material, and the electrolyte will easily enter the material particles and induce various side reactions on the particle surface. These factors will deteriorate the capacity, cycle, rate, gas production and other performances of lithium-ion batteries. Therefore, improving the surface structural stability of single crystal materials has become an important research topic for single crystal ternary cathode materials. Surface coating of single crystal ternary cathode materials is a common modification method, such as coating lithium transition metal oxides (Li2ZrO3, LiCoO2, LiAlO2 and Li2WO4, etc.) and non-electrochemically active metal oxides (Al2O3, ZrO3, MgO and TiO2, etc.).
[0005] Generally, the use of Al2O3 coating is an effective method to improve the surface structural stability of layered lithium transition metal oxide positive electrode materials and reduce the interface side reactions between materials and electrolytes. In non-patent literature (Binghong Han, Baris Key, Saul H. Lapidus, Juan C. Garcia, Hakim Iddir, John T. Vaughey, and Fulya Dogan, Applied Materials & Interfaces (47) 2017: 41291-41302), after high temperature sintering on the surface, Al elements were found in the transition metal layer of the lattice. For nickel-cobalt-manganese layered positive electrode materials, Al2O3 coating will seriously weaken its coating effect and even lead to worse capacity and cycle performance. It can be seen that direct Al2O3 coating is not feasible. For tungsten-coated layered positive electrode materials, only low resistance of the material can be achieved to improve the capacity and rate performance of the material. Non-patent literature (Xinhe Yang, Zicheng Zuo, Haiyan Wang, Quanbin Chen, Hui Zhang, Zhenlei Huang, Borong Wu, Henghui Zhuo, Electrochimica Acta (180) 2015: 604-609) confirmed that the layered material coated with simple tungsten oxide did not generate a stable tungsten compound, which resulted in its enrichment in the graphite negative electrode during the electrochemical reaction, resulting in poor high-temperature cycling and storage performance. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings and defects mentioned in the above background technology, to provide a single crystal nickel cobalt manganese oxide positive electrode material containing Al and W multi-element coating modification and a preparation method thereof, and to use the same in the preparation of a lithium ion battery.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0008] A multi-element coated modified single crystal lithium nickel cobalt manganese oxide positive electrode material, comprising a substrate and a coating layer wrapped on the surface of the substrate, wherein the chemical formula of the substrate is Li a Ni x Co y Mn 1-x-y-z M z O2, wherein 0.9≤a≤1.2, 0.5≤x<1, 0<y≤0.2, 0≤z≤0.1, M includes one or more of Ti, Mg, Y, Al or Zr elements; the coating layer includes tungsten and aluminum elements, the mass of the tungsten element accounts for 0.2%-1.0% of the mass of the positive electrode material matrix, and the aluminum element accounts for 0.03%-0.2% of the mass of the positive electrode material matrix; the coating layer includes Al2(WO4)3.
[0009] Further preferably, the coating layer further includes one or both of Li2WO4 and Li4WO5.
[0010] The multi-component coated modified single crystal lithium nickel cobalt manganese oxide positive electrode material of the present invention is coated together with Al compound, W compound and a small amount of additional lithium source at high temperature, wherein the Al element in the aluminum compound and the W element in the W compound form a stable Al2(WO4)3 substance at high temperature, which effectively inhibits the Al element in the aluminum compound and prevents it from diffusing into the transition metal layer in the material lattice, and forms an aluminum-tungsten compound coating layer on the surface of the material that is beneficial to the stability of the material interface, thereby effectively stabilizing the surface structure of the material; the W compound also reacts with the lithium source and the residual lithium in the material to produce a stable lithium tungstate compound, which effectively reduces the dissolution of the tungsten element in the coating in the electrolyte, promotes its close combination on the surface of the positive electrode material, and can effectively improve the material capacity and power performance.
[0011] Further preferably, the specific surface area of the single crystal nickel cobalt manganese oxide positive electrode material is 0.5 m 2 / g~0.8m 2 / g.
[0012] Further preferably, the particle size range of the above single crystal nickel cobalt manganese oxide positive electrode material is: V 50 is 3.0μm~4.5μm, D V 90 is 6.0μm~8.0μm, D V 99 value <10μm.
[0013] Further preferably, the residual NiO content on the surface of the above-mentioned single crystal nickel cobalt lithium manganese oxide positive electrode material is 300-500ppm of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material, the residual Li2CO3 content is 0.08-0.15% of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material, and the residual LiOH content is 0.04-0.10% of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material.
[0014] As a general inventive concept, the present invention also provides a method for preparing the above-mentioned single crystal nickel cobalt manganese oxide positive electrode material, comprising the following steps:
[0015] S1, mixing a nickel-cobalt-manganese hydroxide precursor, a first lithium source and an M-containing compound and then sintering them for the first time to obtain a matrix;
[0016] S2, mixing the substrate with a second lithium source and a coating agent, wherein the coating agent includes an Al compound and a W compound, and performing a second sintering at a temperature of 750° C. to 950° C. to obtain a multi-component coated and modified single crystal lithium nickel cobalt manganese oxide positive electrode material.
[0017] The second sintering of the present invention is a process of replenishing a small amount of lithium. Since the matrix generated in the S1 process is crushed, there are more micropowder and rock salt phases on the particle surface. The S2 process uses a higher reaction temperature. The lithium source replenished here and the residual lithium on the surface after sintering can undergo sufficient chemical reactions. The metal oxide, as a coating material, can also participate in the chemical reaction, and is carried out almost simultaneously with the repair process of the micropowder and rock salt phase, which is conducive to its close bonding on the surface of the positive electrode material.
[0018] The aluminum compound and tungsten compound added in the second sintering process of the present invention have an unsatisfactory coating effect at low temperature (<600°C), which will cause an increase in the internal resistance and electrochemical polarization of the material, while the single aluminum oxide coating at high temperature (700-900°C) will cause Al to diffuse into the material lattice, and the coating effect is also poor. Through research, it is found that after mixing Al compounds and W compounds with positive electrode materials and sintering at high temperature, the diffusion kinetics of Al elements into the material phase can be significantly inhibited, and finally a composite coating material containing one or more of Al2(WO4)3, Li2WO4 or Li4WO5 is formed on the surface of the positive electrode material, thereby stabilizing the surface structure of the material and improving various material properties.
[0019] Further preferably, the first lithium source and the second lithium source are selected from one or more of lithium carbonate, lithium nitrate, lithium hydroxide or lithium acetate; the molar ratio of the lithium element in the first lithium source to the nickel cobalt manganese hydroxide precursor is 1.0 to 1.2:1; the molar ratio of the lithium element in the second lithium source to the W element in the W compound is 2 to 4:1.
[0020] Further preferably, the above-mentioned M-containing compound is selected from one or more of M-containing carbonates, M-containing hydroxides, M-containing nitrates, M-containing chlorides, M-containing sulfates or M-containing oxides.
[0021] Further preferably, the Al compound includes one or more of aluminum oxide, aluminum hydroxide, and aluminum hydroxide; the W compound includes one or more of tungsten oxide and ammonium tungstate; and the molar ratio of the tungsten element in the W compound to the Al element in the Al compound is 1.5 to 3:1.
[0022] Further preferably, the sintering temperature of the first sintering is 920° C. to 1000° C., and the sintering time is 6 h to 14 h; and the sintering atmosphere of the first sintering is one of oxygen or air.
[0023] Further preferably, the sintering temperature of the second sintering is 800°C to 850°C, and the sintering time is 2h to 12h; the sintering atmosphere of the second sintering is one of oxygen or air. Sintering below 800°C may reduce the stability of the compound formed by Al and W, and the degree of repair of the micropowder and rock salt phase is limited, while if the sintering temperature is too high, the diffusion kinetics of Al element into the material phase may become stronger, affecting the electrochemical properties of the material.
[0024] As a general inventive concept, the present invention also provides a lithium-ion battery, which includes a positive electrode current collector and a positive electrode membrane coated on the positive electrode current collector containing the above-mentioned positive electrode material, a negative electrode current collector and a negative electrode membrane coated on the negative electrode current collector containing the negative electrode material, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the positive electrode material is the above-mentioned multi-element coated modified single crystal nickel cobalt manganese oxide positive electrode material.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] (1) The single crystal nickel cobalt manganese oxide positive electrode material prepared by the present invention has the following advantages: first, it can improve the initial charge / discharge capacity, rate performance and low power problem; second, it can improve the high temperature cycle capacity retention rate of the material at a high charge cut-off voltage; third, it can improve the high temperature storage internal resistance growth and gas production problems of the material at a high charge cut-off voltage; fourth, it can also improve the surface properties of the single crystal nickel cobalt manganese positive electrode material, reduce the residual NiO content on the surface, and reduce the side reactions with the electrolyte during the electrochemical process.
[0027] (2) The present invention prepares a multi-component coated modified single crystal nickel cobalt manganese oxide positive electrode material by using Al compound, W compound and an additional small amount of lithium source to be coated together at high temperature, wherein the Al element in the aluminum compound and the W element in the W compound form a stable Al2(WO4)3 substance at high temperature, which effectively inhibits the Al element in the aluminum compound and prevents it from diffusing into the transition metal layer in the material lattice, and forms an aluminum tungsten compound coating layer on the material surface that is beneficial to the material interface stability, thereby effectively stabilizing the surface structure of the material; the W compound also reacts with the lithium source and the residual lithium in the material to produce a stable lithium tungstate compound, which effectively reduces the dissolution of the tungsten element in the coating into the electrolyte, promotes its close bonding on the surface of the positive electrode material, and can effectively improve the material capacity and power performance.
[0028] (3) The preparation method of the present invention, through high-temperature sintering coating and adding a small amount of lithium source (lithium hydroxide, lithium carbonate or other substances), allows the surface powder and rock salt phase components of the matrix obtained by the first sintering to react with the residual lithium and additional lithium source on the surface and merge with the single crystal particles, thereby improving the material's powder content and reducing the NiO content, thereby improving the material's high-temperature cycle performance.
[0029] (4) The method of the present invention prepares a multi-component coated and modified single-crystal nickel cobalt manganese oxide positive electrode material, wherein the W compound can not only form a lithium-containing coating so that it has the effect of increasing capacity and rate, but also has the effect of weakening the diffusion kinetic behavior of the Al element in the coating; the additionally added lithium source can not only promote the formation of lithium tungsten compounds, but also reduce the content of micropowders and the content of NiO on the surface. Therefore, the present invention combines the W compound with the Al compound and a small amount of lithium source coating, which not only makes up for the deficiency of a single compound coating, but also has a mutual synergistic effect between the three, so that the high capacity, long cycle and high rate characteristics of the positive electrode material are further improved.
[0030] In summary, the present invention modifies the surface of the single crystal nickel cobalt manganese oxide lithium positive electrode material by a multi-component composite coating layer, thereby ultimately ensuring the excellent electrochemical properties of the positive electrode material such as specific capacity, cycle and rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a scanning electron microscope image SEM of the single crystal nickel cobalt manganese oxide positive electrode material prepared in Example 1 of the present invention;
[0033] Figure 2 This is a particle size volume distribution diagram of the single crystal nickel cobalt manganese oxide positive electrode material prepared in Example 1 of the present invention;
[0034] Figure 3 This is an XPS graph of the single crystal nickel cobalt manganese oxide positive electrode material prepared in Example 1 of the present invention;
[0035] Figure 4 This is a scanning electron microscope image SEM of the single crystal nickel cobalt lithium manganese oxide positive electrode material prepared in Comparative Example 1;
[0036] Figure 5 This is the particle size volume distribution diagram of the single crystal nickel cobalt manganese oxide positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0038] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0040] Embodiment 1:
[0041] A multi-element coated modified single crystal lithium nickel cobalt manganese oxide positive electrode material, comprising a positive electrode material matrix Li 1.02 Ni 0.666 Co 0.08 Mn 0.25 Zr 0.004 O2 and a tungsten-containing compound coating layer coated on the surface of the substrate: Al2(WO4)3, Li2WO4, Li4WO5; among them, tungsten element accounts for 0.5% of the mass of the positive electrode material matrix, and aluminum element accounts for 0.04% of the mass of the positive electrode material matrix.
[0042] The method for preparing the multi-element coated modified single crystal lithium nickel cobalt manganese oxide positive electrode material of this embodiment comprises the following steps:
[0043] (1) The purchased nickel cobalt manganese hydroxide precursor Ni 0.67 Co 0.08 Mn 0.25After (OH)2, LiOH·H2O and nano zirconium oxide were mixed evenly in a molar ratio of 1:1.02:0.004, the mixed materials were sintered at a constant temperature of 950°C for 12 hours in an oxygen atmosphere (oxygen concentration>96%), cooled, crushed, and passed through a 200-mesh sieve to obtain the positive electrode material matrix lithium transition metal oxide. The molecular formula of the positive electrode material was Li 1.02 Ni 0.666 Co 0.08 Mn 0.25 Zr 0.004 O2.
[0044] (2) The positive electrode material matrix obtained in step (1) is uniformly mixed with 0.055 mol of nano-WO3 (the mass ratio of W element to the positive electrode material matrix is 0.5%), 0.014 mol of nano-Al2O3 (the mass ratio of Al element to the positive electrode material matrix is 0.04%) and 0.22 mol of LiOH·H2O to form a mixture; then the mixture is placed in a kiln for calcination under the following sintering conditions: air atmosphere, 3°C / min rising to 830°C for 10 hours, and naturally cooling to room temperature. The obtained material is sieved through a 200-mesh screen to obtain a final tungsten-containing composite coated single crystal nickel cobalt lithium manganese oxide positive electrode material.
[0045] pass Figure 1 Scanning electron microscopy observations show that the surface of the coated sample is relatively smooth and has fewer fine powder particles ( Figure 2 The particle size volume distribution is lower than Dv1 area (no peak), with fine dot-like coating, and the specific surface area is 0.658m 2 / g, Dv50 value is 3.7μm, D V 90 value is 7.2um, D V The value of 99 is 8.6 μm. According to ICP test, the residual NiO content on the surface of the sample after composite coating is 300 ppm, which is relatively low, which is beneficial to alleviate the adverse phase change during the cycle and improve the structural stability.
[0046] pass Figure 3 From the XPS images, we can see that the main components of tungsten compounds on the surface of the coated sample are Al2(WO4)3, Li2WO4 and Li4WO5, which not only form stable Al2(WO4)3 substances, effectively inhibit the Al element in the aluminum compound and prevent it from diffusing into the transition metal layer in the material lattice, but also form an aluminum-tungsten compound coating on the material surface that is beneficial to the stability of the material interface, effectively stabilizing the surface structure of the material; and the W element also reacts with the lithium source and residual lithium in the material to produce stable lithium tungstate compounds, effectively reducing the dissolution of tungsten elements in the coating in the electrolyte, promoting its close bonding on the surface of the positive electrode material, and effectively improving the material capacity and power performance.
[0047] Embodiment 2:
[0048] The difference between this embodiment and embodiment 1 is that in step (2): 0.0079 mol of ammonium tungstate is weighed, and the mass ratio of tungsten element to positive electrode material matrix is 0.5%; the sintering conditions are: air atmosphere, 3°C / min rising to 850°C and keeping warm for 10 hours, and the other process parameters are the same as those in embodiment 1.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is step (2): weighing 0.028 mol of aluminum hydroxide, the mass ratio of aluminum element to positive electrode material matrix is 0.05%; the sintering conditions are: air atmosphere, 3°C / min rising to 800°C and keeping warm for 10 hours, and the other process parameters are the same as those in embodiment 1.
[0051] Comparative Example 1:
[0052] This comparative example is the positive electrode material matrix lithium transition metal oxide Li prepared in step (1) of Example 1 1.02 Ni 0.666 Co 0.08 Mn 0.25 Zr 0.004 O2. Figure 4 This is a scanning electron microscope image (SEM) of the single crystal nickel cobalt lithium manganese oxide positive electrode material prepared in Comparative Example 1. Figure 5 This is the particle size volume distribution diagram of the single crystal nickel cobalt manganese oxide positive electrode material prepared in Comparative Example 1.
[0053] Comparative Example 2:
[0054] The step (1) of this comparative example is completely consistent with that of Example 1, except that, in step (2), only 0.22 mol of LiOH·H2O is weighed and mixed with the positive electrode material matrix, and the other process parameters are the same as those of Example 1;
[0055] Comparative Example 3:
[0056] The step (1) of this comparative example is completely consistent with that of Example 1, except that, in step (2): only 0.055 mol of WO3 (the mass ratio of tungsten element to positive electrode material matrix is 0.5%) is weighed and mixed with the positive electrode material matrix, and the other process parameters are the same as those of Example 1;
[0057] Comparative Example 4:
[0058] The step (1) of this comparative example is completely consistent with that of Example 1. The difference is that, in step (2): only 0.055 mol of WO3 (the mass ratio of tungsten element to the positive electrode material matrix is 0.5%) and 0.014 mol of Al2O3 (the mass ratio of aluminum element to the positive electrode material matrix is 0.04%) are weighed and mixed with the positive electrode material matrix, and the other process parameters are the same as those of Example 1;
[0059] Comparative Example 5:
[0060] Step (1) of this comparative example is completely consistent with that of Example 1, except that, in step (2), the sintering conditions are: air atmosphere, heating to 700°C at 3°C / min and keeping for 10 h, and then naturally cooling to room temperature. The other process parameters are the same as those of Example 1.
[0061] The battery positive electrode materials prepared in the examples and comparative examples were mixed with conductive carbon black and binder PVDF in a mass ratio of 92:5:3, and then coated on Al foil with NMP as solvent, dried at 120°C for 12h, rolled and punched into 12mm discs, and assembled into CR2032 button batteries with metal lithium sheets as negative electrodes in an argon-protected glove box (oxygen content less than 1ppm, moisture less than 1ppm), and electrochemical performance tests were carried out at 25°C and 3.0-4.45V voltage window. The specific test system is: 0.1C charging and 0.1C discharging in the first week; 0.2C charging and 0.2C discharging in the second week; 0.2C charging and 0.5C discharging in the third week; 0.2C charging and 1C discharging in the fourth week; 0.2C charging and 1C discharging in the fifth week; 1C charging and 1C discharging in the sixth to fifth weeks. The electrochemical data of the button cells assembled from the materials obtained in the above embodiments and comparative examples, such as the 0.1C discharge specific capacity, 2C discharge specific capacity, 50-week cycle capacity retention rate (ratio of the discharge specific capacity at the 55th week to the discharge specific capacity at the 6th week), and the surface NiO content, residual lithium, and micropowder content of the materials are shown in Table 1.
[0062] Table 1: Electrochemical data of each embodiment and comparative example, as well as surface NiO content, residual lithium, and micropowder content of the material
[0063]
[0064] As can be seen from the data in Table 1, comparing Example 1 with Comparative Example 1, the performance of the tungsten-containing composite coating is better, the material has better electrochemical performance, lower residual lithium, residual NiO and lower micropowder content; comparing Example 1 with Comparative Example 5, it is shown that tungsten oxide, aluminum oxide and lithium source coating have ideal effects only at high temperatures, and high temperature will promote the production of tungsten-containing composite materials and inhibit the Al element from entering the lattice of the material, further illustrating the advantages of the composite coating modification method. Comparing Example 1 with Comparative Example 4, it is shown that although tungsten oxide and aluminum oxide can react with residual lithium to significantly reduce residual lithium under high temperature coating, because no additional lithium is added, lithium is insufficient, resulting in less lithium tungstate production content, and weak improvement in material capacity and rate performance.
[0065] Comparing Example 1 and Comparative Example 3, it is shown that although tungsten oxide can react with residual lithium and an external lithium source under high-temperature coating to fully produce lithium tungstate, which significantly improves the material capacity and rate performance, Al2O3 is not added, resulting in poor cycle and internal resistance growth performance. Compared with the once sintered material of Comparative Example 1, the content of NiO, Li2CO3 and LiOH on the surface of the coated material is significantly reduced, which can improve the manufacturing and processing performance of the pole piece and reduce the gas production behavior of the lithium-ion battery. After the single crystal positive electrode material is modified by high-temperature composite coating, it has the advantages of a single coating and makes up for the shortcomings of a single coating. The lithium-ion battery composed of this material as the active material has high capacity, high rate, long cycle and low internal resistance growth characteristics.
[0066] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A multi-component coated and modified single crystal lithium nickel cobalt manganese oxide positive electrode material, characterized in that: It includes a substrate and a coating layer wrapped on the surface of the substrate, wherein the chemical formula of the substrate is Li a Ni x Co y Mn 1-x-y-z M z O2, wherein 0.9≤a≤1.2, 0.5≤x<1, 0<y≤0.2, 0≤z≤0.1, and M includes one or more of Ti, Mg, Y, Al or Zr elements; The coating layer includes tungsten and aluminum elements, the mass of the tungsten element accounts for 0.2%-1.0% of the mass of the positive electrode material matrix, and the aluminum element accounts for 0.03%-0.2% of the mass of the positive electrode material matrix; the coating layer includes Al2(WO4)3; The coating layer also includes one or both of Li2WO4 and Li4WO5.
2. The single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: The specific surface area of the single crystal nickel cobalt manganese oxide positive electrode material is 0.5 m 2 / g~0.8m 2 / g.
3. The single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: The particle size range of the single crystal nickel cobalt manganese oxide positive electrode material is: V 50 is 3.0μm~4.5μm, D V 90 is 6.0μm~8.0μm, D V 99 value <10μm.
4. The single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: The residual NiO content on the surface of the single crystal nickel cobalt lithium manganese oxide positive electrode material is 300-500ppm of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material, the residual Li2CO3 content is 0.08-0.15% of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material, and the residual LiOH content is 0.04-0.10% of the mass of the single crystal nickel cobalt lithium manganese oxide positive electrode material.
5. A method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing a nickel-cobalt-manganese hydroxide precursor, a first lithium source and an M-containing compound and then sintering them for the first time to obtain a matrix; S2, mixing the substrate with a second lithium source and a coating agent, wherein the coating agent includes an Al compound and a W compound, and performing a second sintering at a temperature of 750° C. to 950° C. to obtain a multi-component coated and modified single crystal lithium nickel cobalt manganese oxide positive electrode material.
6. The method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 5, characterized in that: The first lithium source and the second lithium source are selected from one or more of lithium carbonate, lithium nitrate, lithium hydroxide or lithium acetate; the molar ratio of the lithium element in the first lithium source to the nickel cobalt manganese hydroxide precursor is 1.0 to 1.2:1; the molar ratio of the lithium element in the second lithium source to the W element in the W compound is 2 to 4:
1.
7. The method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 6, characterized in that: The M-containing compound is selected from one or more of M-containing carbonates, M-containing hydroxides, M-containing nitrates, M-containing chlorides, M-containing sulfates or M-containing oxides.
8. The method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 7, characterized in that: The Al compound includes one or more of aluminum oxide, aluminum hydroxide, and aluminum hydroxide; the W compound includes one or more of tungsten oxide and ammonium tungstate; and the molar ratio of the tungsten element in the W compound to the Al element in the Al compound is 1.5-3:
1.
9. The method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to any one of claims 5 to 8, characterized in that: The sintering temperature of the first sintering is 920° C. to 1000° C., and the sintering time is 6 hours to 14 hours; the sintering atmosphere of the first sintering is one of oxygen or air.
10. The method for preparing a single crystal nickel cobalt lithium manganese oxide positive electrode material according to claim 9, characterized in that: The sintering temperature of the second sintering is 800° C. to 850° C., and the sintering time is 2 h to 12 h; the sintering atmosphere of the second sintering is one of oxygen and air.
11. A lithium ion battery comprising a positive electrode current collector and a positive electrode film coated on the positive electrode current collector containing a positive electrode material, a negative electrode current collector and a negative electrode film coated on the negative electrode current collector containing a negative electrode material, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte, characterized in that: The positive electrode material is the single crystal nickel cobalt lithium manganese oxide positive electrode material according to any one of claims 1 to 10.
Citation Information
Patent Citations
High-capacity monocrystalline high-nickel positive electrode material for lithium battery and preparation method of high-capacity monocrystalline high-nickel positive electrode material for lithium battery
CN107768619A
A high-nickel cathode material, a preparation method thereof, and a lithium ion battery
CN109244436A
High-rate ternary positive electrode material as well as preparation method and application thereof
CN114335547A
Modified high-nickel monocrystal nickel cobalt lithium manganate positive electrode material, preparation method thereof and lithium ion battery
CN114784265A